O Ofício das Rezadeiras: um estudo antropológico sobre as práticas terapêuticas e a comunhão de crenças em Cruzeta/RN - Santos, Francimário Vito dos (2007)
The present Master´s dissertation aims to study the practices of the rezadeiras, Brazilian women healers, through an anthropological perspective. Special attention will be given to the understanding of these practices as a dynamic process in relation to those women who heal in Cruzeta (Seridó, Rio Grande do Norte), where is located our ethnographic research. For this research, twenty four rezadeiras were contacted and colaborated with our work plan. Among them, two were pentecostal rezadeiras and another one was member of the Jurema cult, an afro-brazilian religious cult. Similarities among these women healers were perceived in the research process, mostly in terms of their learning process and the use of certain objects and ritual techniques. However, apparent differences among them gave us the chance for understanding and reflecting on the actual heterogeneity of this world of specialists. Furthermore, i tried to capture the relations between the rezadeiras and the therapeutic practices from health professionals or the religious practices of religious leaders (Catholic, pentecostal, etc). It is possible to ascertain about the complementarity between therapeutic practices from different cultural logics. This complementarity is also perceived through the religious interchanges and transits among different healers, including those who have different religious beliefs. In this work, rituals are also described and they are a crucial factor to the understanding of this particular religious and therapeutic practice conducted by women. Following these ideas, our basic aim is to understand how the rezadeiras make interpretations about health and illness, specially those ones which are particular associated with their practices, the so called "doenças de rezadeiras"